Understanding the near-peer relationship: Resident perspectives around a novel on-call workplace-based assessment - Lu, Amy D; Atkinson, Adelle R; Johnstone, Julie C (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Background: Workplace-based assessment (WBA) is a critical component of competency-based medical education (CBME), though literature on WBA for overnight call is limited. We evaluated a WBA tool completed by supervising subspecialty trainees on paediatric residents during subspecialty overnight call, for usefulness facilitating feedback/coaching in this setting.Methods: Web-based surveys were sent to residents pre- and post-WBA tool implementation monthly for four months (August-December 2018), exploring feedback frequency, Likert-scaled opinions of tool feasibility/usefulness facilitating feedback, and qualitative experiences. Assessor comments were categorized as actionable/non-actionable. Quantitative data was summarized using descriptive statistics. Qualitative data was coded to identify themes. Results: Total response rates averaged 41% (total 25 responses, average five respondents/12 residents on-call each month). Post-implementation (n = 16 responses), a non-sustained trend of increased Medical Expert feedback was observed. Residents were generally divided or disagreed on tool usefulness facilitating feedback and feasibility. Comments contained actionable feedback in < 10% of completed WBAs. Qualitative analysis revealed barriers to tool-facilitated coaching including: feedback quality and setting/environment, role of senior near-peer as assessor, interpersonal burden in encounters, and tool-specific issues.Conclusions: Increasing frequency of WBA tool completion is not sufficient to achieve CBME goals. Factors impacting feedback/coaching within the resident/near-peer dyad must be addressed.